1975
DOI: 10.3382/ps.0541962
|View full text |Cite
|
Sign up to set email alerts
|

The Anemia Caused by Aflatoxin

Abstract: The effects of graded doses of dietary aflatoxin (0, 0.625, 1.25, 2.5, 5.0, and 10.0 mug./g.) on hemoglobin, packed blood cell volume, erythrocyte count, leucocyte counts, bone marrow lipid, and bone marrow nucleic acids of chickens were measured. The hemoglobin, packed cell volume, and erythrocyte count were reduced significantly (P less than 0.05) to about the same extent by any given dose. Microscopic examination of stained smears of the bone marrow revealed a hyperplastic response including the granulocyti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
48
1
7

Year Published

1982
1982
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(67 citation statements)
references
References 22 publications
10
48
1
7
Order By: Relevance
“…The mean packed cell volumes of all treatment groups of wild turkey poults were increased compared with controls, which contrasts with previous reports of decreased packed cell volumes (Weibking et al, 1994) and hemolytic anemia (Tung et al, 1975) in aflatoxin-exposed domestic poults. It is unknown whether the increased hematocrits seen in our wild turkeys were a direct effect of aflatoxin exposure, or whether they were secondary to other conditions.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…The mean packed cell volumes of all treatment groups of wild turkey poults were increased compared with controls, which contrasts with previous reports of decreased packed cell volumes (Weibking et al, 1994) and hemolytic anemia (Tung et al, 1975) in aflatoxin-exposed domestic poults. It is unknown whether the increased hematocrits seen in our wild turkeys were a direct effect of aflatoxin exposure, or whether they were secondary to other conditions.…”
Section: Discussioncontrasting
confidence: 56%
“…Because the anemia induced by aflatoxins in chickens begins after 17 to 21 days of aflatoxin ingestion (Huff et al, 1986), it may be that a more prolonged feeding trial in wild turkeys would be necessary for such an anemia to develop. Bone marrow granulocytic hyperplasia has been speculated to be the cause of heterophilia in chickens fed aflatoxin (Tung et al, 1975), but alternate explanations for the heterophilia seen in our poults includes an inflammatory response or a response to stress such as is observed in chickens (Siegel, 1971).…”
Section: Discussionmentioning
confidence: 91%
“…These findings are in concurrence with Tung et al, (1975); Lanza et al, (1980); Balachandran and Ramakrishnan (1987) and Vasan et al, (1998).…”
Section: The Effects Of Supplementation Of Curcuma Longa On Haematolosupporting
confidence: 80%
“…Hemoglobin concentration was depressed analogous to PCV, reflecting anaemia. Tung et al, (1975) also observed anaemia and suggested that aflatoxin associated anaemia as hemolytic anaemia characterized by decreased erythrocyte counts, packed cell volume, hemoglobin levels. This type of anaemia could result from inhibition of haematopoiesis, defective haematopoiesis, increased destruction of red blood cells, or a combination of all the three (Huff et al, 1986).…”
Section: The Effects Of Supplementation Of Curcuma Longa On Haematolomentioning
confidence: 99%
“…Este aumento no percentual de linfócitos pode estar relacionado à diminuição da atividade de células fagocitárias causada pela AFB 1 (CHANG & HAMILTON, 1979), uma vez que todos os grupos alimentados com ração contendo as micotoxinas apresentaram uma redução (P<0,05) no percentual de heterófilos, apesar de não ter havido diferença no percentual de monócitos (P>0,05). A diminuição do número de leucócitos observada no presente estudo é coerente com os dados descritos por JAVED et al (1995), porém contrária aos resultados obtidos por TUNG et al (1975 Resultados expressos em média + desvio padrão, para 4 repetições. a-c Médias seguidas de letras distintas, em uma mesma coluna, diferem pelo teste de Fisher (P < 0,05).…”
Section: Introductionunclassified